Bioactivity Study of Modified Chlorophyll a Compound on Staphylococcus aureus - Dewi Wahyuningrum, Surya
Chlorophyll is a natural pigment that has a high abundance. The structure of chlorophyll was modified in order to study the potential of chlorophyll as a photosensitizer in Photodynamic Inactivation or Photodynamic Therapy. Modification of the structure of chlorophyll that has been done by previous researchers, such as replacing the center Mg2 + ion with other metal ions that have a +2 oxidation state and have similar ionic sizes, and replacing the phytol side chain. In this study, chlorophyll was isolated from spinach using a solvent mixture of acetone-dioxane-water. Chlorophyll a successfully separated from carotene, chlorophyll b, pheophytin a, and pheophytin b using sucrose column chromatography with petroleum ether and diethyl ether 10% (v / v) in petroleum ether as the eluent. The TLC test results showed Rf value of chlorophyll a was 0,56. The maximum absorption of chlorophyll a in the visible light region is at 429.5 nm and 661.5 nm, respectively the Soret band and Q. The center metal ion of chlorophyll a was replaced with the first series transition metal ions, such as Fe2+, Zn2+, Cu2+ and Co2+ in order to improve the performance of the compound as a photosensitizer. Generally, the pattern of absorption bands of the modified chlorophyll a were relatively similary, despite a shift in Soret and Q bands. The Soret and Q bands of Zn-pheophytin a, Cu-pheophytin a, Co-pheophytin a and Fe-pheophytin a respectively were 422,5 nm and 655,5 nm; 421,5 nm and 651 nm; 432 nm and 661 nm; 400 nm and 654,5 nm. The fluorescence measurements results showed the trend of intensities are Zn-pheophytin a> Fe-pheophytin a> Co-pheophytin a> Cu-pheophytin a. Generally, the modified chlorophyll a has fluorescence intensity lower than chlorophyll a, except Zn-pheophytin a. Photodynamic inactivation potential of modified chlorophyll a was studied on the growth of Staphylococcus aureus under irradiation of a red LED with ?=650 m and its incubated at 37 oC for 24 hours. The results show that Zn-pheophitin a has potential as a antibacterial under this condition. While the Cu-pheophitin a, Co-pheophitin a, and Fe-pheophitin a did not able to inhibit the the growth of Staphylococcus aureus under this condition.